Analisis Ekspor Kakao Olahan Indonesia ke Sembilan Negara Tujuan Tahun 2000–2014 - Maulana, Arif; Kartiasih, Fitri (UI Scholars Hub, 2017)
The objectives of this article is to analyze the competitiveness of Indonesias processed cocoa export to nine destination countries and to investigate the determinants of export volumes of Indonesias cocoa. Two analysis is conducted using revealed comparative advantage (RCA) and panel data regression. The result indicates that Indonesian processed cocoa has a high comparative advantage in Spain, while in Singapore has a comparative advantage at worst. The panel data regression estimates showed that GDP, population, RCA, and tax policy was statistically significant and had positive effect to cocoa export volumes but the price of processed cocoa had negative effect.